Syntactic Semantics in Surah Al-Qasas - Abdullah, Naatiq Najm (Thi Qar Arts Journal, 2024)
The Holy Quran, a book of guidance, uses language as its medium and has managed to elevate it from general usage to specific semantic significance. Its language is miraculous in usage, not in structure; because the latter is the domain of all who speak this language. This represents one of the most complex stages that provoke debate and evoke feeling, making the relationships in the language of the Holy Quran primarily relationships of meanings.Given that the syntactic level is one of the most active levels in expressing the semantics of words through the syntactic relationships that link them with others within structures, it has become an important axis in the study of meaning. Hence, the idea of studying syntactic semantics in Surah Al-Qasas emerged due to its importance in linguistic studies. The research was divided into three discussions, concluded with a summary.The first discussion was dedicated to studying the topics of definiteness and indefiniteness, addressing their definitions linguistically and terminologically, along with explaining the semantics of each. Surah Al-Qasas includes various implications of indefiniteness such as “the intention of informing to affirm the predicate to the subject without the desire for a specific reference or specification, the intention of generality and absoluteness, magnification, exaggeration, disregard and mockery, and denial,” while the implications of definiteness in the Surah were the subject of research.